Evolution of Reading Literacy, or The New Adventures of the Push Me Pull You - Galina Tsukerman; Galina Kovaleva; Marina Kuznetsova (Voprosy obrazovaniya / Educational Studies Moscow, 2015)
The Push–Pull tool is a combination of the PIRLS and PISA tests designed to assess literacy among school students of 4–9 grades and based around informational texts. The method allows to assess the dynamics of reading literacy among individuals and groups of school students. The paper presents data from three samples of school students who answered the Push–Pull questions twice in one or two years. All the samples reveal the same regular patterns: considerable progress in literacy among those who scored low the first time, and regress among those who initially performed the best. Besides, great differences were found between the best performers of the test in Russia and their counterparts in the OECD countries, which means regress among the best reading students has nothing to do with the processes of age-related development. Instead, it is explained through the culture-specific development tools and the lack of teaching methods required to ensure further expansion of the reading elite.